2012
DOI: 10.1136/annrheumdis-2011-200795
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of arterial lesions in Takayasu's arteritis and giant cell arteritis

Abstract: Objectives To compare patterns of arteriographic lesions of the aorta and primary branches in patients with Takayasu’s arteritis (TAK) and giant cell arteritis (GCA). Methods Patients were selected from two North American cohorts of TAK and GCA. The frequency of arteriographic lesions was calculated for 15 large arteries. Cluster analysis was used to derive patterns of arterial disease in TAK versus GCA and in patients categorised by age at disease onset. Using latent class analysis, computer derived classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(151 citation statements)
references
References 17 publications
(15 reference statements)
7
137
0
3
Order By: Relevance
“…Cluster analysis revealed that TAK lesions mostly develop in a symmetric manner in paired vascular territories and disease extension is contiguous in the aorta (14). A similar finding was also observed in the case of GCA (15). Computer-derived classification models distinguished TAK from GCA in 2 subgroups, defining 26% and 18% of the study sample, respectively; however, 56% of patients were classified into a subgroup that did not strongly differentiate between TAK and GCA.…”
Section: Clinical Coursesupporting
confidence: 61%
See 1 more Smart Citation
“…Cluster analysis revealed that TAK lesions mostly develop in a symmetric manner in paired vascular territories and disease extension is contiguous in the aorta (14). A similar finding was also observed in the case of GCA (15). Computer-derived classification models distinguished TAK from GCA in 2 subgroups, defining 26% and 18% of the study sample, respectively; however, 56% of patients were classified into a subgroup that did not strongly differentiate between TAK and GCA.…”
Section: Clinical Coursesupporting
confidence: 61%
“…However, the limitations of physical examination were recently shown in a study comparing physical signs with imaging data (15). When bruits, absent pulses, or blood pressure differences are evaluated as physical signs, the presence of any single item has a sensitivity of 52%-71% and a specificity of 59%-86%.…”
Section: Physical Examinationmentioning
confidence: 99%
“…To identify the clustering patterns of lung abnormalities on chest CT images, latent class analysis was performed. An optimal number of latent classes was determined using model fit statistics such as Bayesian information criterion (BIC) and consistent Akaike information criterion (CAIC) values (24,25). Latent class analysis was performed using SAS version 9.3 (SAS Institute) and PROC LCA (26), whereas other statistical analyses were performed using SPSS version 21.0 (IBM Japan).…”
Section: Methodsmentioning
confidence: 99%
“…As recent observations have shown that the histopathology of arterial lesions in these 2 diseases is difficult to distinguish, it is speculated whether TA and GCA are part of a spectrum of manifestations within a single disease (5). On angiography, arteriographic lesions are recognized as the sequelae of inflammation; strong similarities and subtle differences in these lesions were observed between GCA and TA (6).…”
Section: To the Editormentioning
confidence: 99%